2018
DOI: 10.1182/blood-2018-99-112991
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability and Response Rates of Daratumumab in Patients with Relapsed Light Chain (AL) Amyloidosis: Results of a Phase II Study

Abstract: Daratumumab is a human IgG1k monoclonal antibody targeting the CD38 surface antigen on plasma cells with proven efficacy in multiple myeloma. While biology of clonal plasma cells in AL amyloidosis is distinct from myeloma, clonal plasma cells in AL amyloidosis express surface CD38, providing a rationale for using daratumumab. Infusion-related reactions (IR) of 48% were reported in patients who had daratumumab as monotherapy for relapsed multiple myeloma. Therefore, we designed a clinical trial to study tolerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
1
15
0
6
Order By: Relevance
“…In a phase II trial, the oral proteasome inhibitor ixazomib induced hematologic response in 56% of 21 previously treated patients, with all the 5 patients who had not been previously exposed to bortezomib achieving at least VGPR, and is currently being tested in a randomized phase III trial in patients with relapsed and/or refractory disease (NCT01659658) 145 . The humanized anti-CD38 monoclonal antibody daratumumab, is one of the most promising new agents 146,147 and is being moved to frontline therapy in clinical trials. A recently published series of previously treated individuals who received daratumumab reported a rapid (median 1 months) hematologic response in 76% of patients with 36% complete responses 148 .…”
Section: [H2] Patient Risk Stratificationmentioning
confidence: 99%
“…In a phase II trial, the oral proteasome inhibitor ixazomib induced hematologic response in 56% of 21 previously treated patients, with all the 5 patients who had not been previously exposed to bortezomib achieving at least VGPR, and is currently being tested in a randomized phase III trial in patients with relapsed and/or refractory disease (NCT01659658) 145 . The humanized anti-CD38 monoclonal antibody daratumumab, is one of the most promising new agents 146,147 and is being moved to frontline therapy in clinical trials. A recently published series of previously treated individuals who received daratumumab reported a rapid (median 1 months) hematologic response in 76% of patients with 36% complete responses 148 .…”
Section: [H2] Patient Risk Stratificationmentioning
confidence: 99%
“…54 Other investigators noted similar results; excellent hematologic and organ responses were observed in the majority of the patients treated with single-agent daratumumab and with daratumumab in combination with other agents. 55,56 In conclusion, daratumumab as a single agent is now a backbone of therapy with single-agent activity similar to that of PIs and IMiDs. The demonstration of its safety (with minimal additional toxicity) and confirmation of its efficacy with other antimyeloma agents in improving the depth and duration of responses led to combination trials.…”
Section: Daratumumab In Al Amyloidosismentioning
confidence: 99%
“…Renal and cardiac response at six months of treatment was reached by 37·5% (3/8) and 40% (4/10) of patients respectively. There was no grade 3 IRR and 66% of patients experienced respiratory illnesses (Sanchorawala et al , ). Another phase II prospective study of daratumumab in monotherapy was updated at the Annual Congress of European Hematology Association in 2018 by Jaccard.…”
Section: Monoclonal Antibodies Targetting Plasma Cell Clonementioning
confidence: 99%